Longifolioside A inhibits TLR4-mediated inflammatory responses by blocking PKCδ activation in LPS-stimulated THP-1 macrophages. (July 2020) - Lee, Su Ui; Oh, Eun Sol; Ryu, Hyung Won; Kim, Mun-Ock; Kang, Myung-Ji; Song, Yu Na; Lee, Ro Woon; Kim, Doo-Young; Ro, Hyunju; Jung, Sunin; Hong, Sung-Tae; Oh, Sei-Ryang
Abstract: Longifolioside A is an iridoid glucoside compound isolated from Pseudolysimachion rotundum var . subintegrum, which has been used in traditional herbal medicines to treat respiratory inflammatory diseases. Logifolioside A is a potent antioxidant; however, its underlying pharmacological mechanisms of action in inflammatory diseases are unknown. Here, we investigated the inhibitory effects of longifolioside A in lipopolysaccharide (LPS)-stimulated toll-like receptor 4 (TLR4) signal transduction systems using human THP-1 macrophages and HEK293 cells stably expressing human TLR4 protein (293/HA-hTLR4). Longifolioside A significantly reduced the release of inflammatory cytokines such as interleukin (IL)-6, -8, and tumor necrosis factor (TNF)-α in LPS-stimulated THP-1 macrophages. Furthermore, longifolioside A inhibited the expression of inflammatory mediator genes such as inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 that produce nitric oxide (NO) and prostaglandin E2 (PGE2), respectively. Longifolioside A suppressed the phosphorylation of PKCδ, IRAK4, IKKα/β, IκBα, and mitogen-activated protein (MAP) kinases (ERK 1/2 and JNK, but not p38), thereby inactivating the nuclear localization of NF-κB and AP-1, and thus decreasing the expression of inflammatory response genes. Notably, longifolioside A disrupted the interaction between human TLR4 and the TIR domain-containing adaptor protein (TIRAP), an early step during TLR4 activation, thereby reducing IL-8 secretion in 293/HA-hTLR4 cells. This inhibitory effect was comparable to that of TAK-242 (a TLR4 inhibitor, or resatorvid). Our results indicate that longifolioside A prevents inflammatory response by suppressing TLR4 activation required for NF-κB and AP-1 activation.